Multiple mechanisms quench passive spiral galaxies - Fraser-McKelvie, Amelia; Brown, Michael J. I.; Pimbblet, Kevin; Dolley, Tim; Bonne, Nicolas J. (Oxford University Press, 2018)
We examine the properties of a sample of 35 nearby passive spiral galaxies in order to determine their dominant quenching mechanism(s). All five low-mass (M⋆ < 1 × 1010 M⊙) passive spiral galaxies are located in the rich Virgo cluster. This is in contrast to low-mass spiral galaxies with star formation, which inhabit a range of environments. We postulate that cluster-scale gas stripping and heating mechanisms operating only in rich clusters are required to quench low-mass passive spirals, and ram-pressure stripping and strangulation are obvious candidates. For higher mass passive spirals, while trends are present, the story is less clear. The passive spiral bar fraction is high: 74 ± 15 per cent, compared with 36 ± 5 per cent for a mass, redshift and T-type matched comparison sample of star-forming spiral galaxies. The high mass passive spirals occur mostly, but not exclusively, in groups, and can be central or satellite galaxies. The passive spiral group fraction of 74 ± 15 per cent is similar to that of the comparison sample of star-forming galaxies at 61 ± 7 per cent. We find evidence for both quenching via internal structure and environment in our passive spiral sample, though some galaxies have evidence of neither. From this, we conclude no one mechanism is responsible for quenching star formation in passive spiral galaxies – rather, a mixture of mechanisms is required to produce the passive spiral distribution we see today.